2020
DOI: 10.1007/s10311-020-00991-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of environmentally persistent free radicals and reactive oxygen species during the thermal treatment of soils contaminated by polycyclic aromatic hydrocarbons

Abstract: Environmentally persistent free radicals (EPFRs) are emerging contaminants of increasing concern due to their toxicity for life and ecosystems, yet their formation, behavior and fate are poorly known. In particular, there is actually no knowledge on the formation of those radicals during the thermal treatment of soils containing polycyclic aromatic hydrocarbons. Such knowledge is important because thermal treatment is a remediation method used to decontaminate soils by removing and degrading PAHs. Here, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Results show strong PFRs signals in heated soils, maximizing at 300 °C, and almost no signal for the unheated anthracene-spiked soils (Figure S3) and heated raw soils without anthracene (Figure S1). This finding confirms that PFRs signals are induced by both heating and the presence of PAHs, as shown for benzo[a]pyrene-spiked soils heated at 100-200 °C (Liu et al 2020). Rising the temperature was also necessary to form PFRs during adsorption of dichlorobenzene on cupric oxidecontaining particles at 100-400 °C (Lomnicki et al 2008).…”
Section: Effect Of Soil Heating On Persistent Free Radicalssupporting
confidence: 85%
See 4 more Smart Citations
“…Results show strong PFRs signals in heated soils, maximizing at 300 °C, and almost no signal for the unheated anthracene-spiked soils (Figure S3) and heated raw soils without anthracene (Figure S1). This finding confirms that PFRs signals are induced by both heating and the presence of PAHs, as shown for benzo[a]pyrene-spiked soils heated at 100-200 °C (Liu et al 2020). Rising the temperature was also necessary to form PFRs during adsorption of dichlorobenzene on cupric oxidecontaining particles at 100-400 °C (Lomnicki et al 2008).…”
Section: Effect Of Soil Heating On Persistent Free Radicalssupporting
confidence: 85%
“…oxidation, has also been evidenced recently during the removal of benzo [a]pyrene-spiked soils at 100-200 °C, despite desorption being considered as the main removal mechanism (Jia et al 2020). We also found that the transformation of benzo[a]pyrene in heated soils induces the formation of persistent free radicals (PFRs) (Liu et al 2020). Since thermal treatment is commonly applied to clean PAH-contaminated soils (Kuppusamy et al 2016), this remediation technique may pose potential health risks due to the formation of PFRs.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations